Dīwān Abū Bakr al-Khwārazmī : Maʿa dirāsa li-ʿaṣrihi wa-ḥayātihi wa-shiʿrihi - Khwārazmī, Abū Bakr (Miras Maktoob, ISBN: 9789004365452., 2019)
Born and raised in Khwārazm, Abū Bakr Khwārazmī (d. 383/993) grew up to become an authority on the Arabic language, despite his foreign origin. He spent his adult life away from his homeland, at the courts of the powerful of his time. We thus find him in Aleppo enjoying the generosity of Sayf al-Dawla, in Bukhara living off the largesse of the vizier al-Balʿamī, or in Nishapur, earning his keep by singing the praises of Amīr Aḥmad al-Mīkālī. Abū Bakr's life was not without conflict, which may partly explain his wanderings. He is mostly admired as a gifted writer of letters, which he composed in rhymed, ornate prose. It is said that he died soon after he lost a contest with upcoming talent Badīʿ al-Zamān al-Hamadhānī. His poetry was less well received and thusfar never published. Whether this was deservedly the case, we can now decide for ourselves by consulting the divan's present, first edition.